Analisis Faktor-Faktor Resiko Pekerjaan Bor Pile, Balok, Dan Kolom Pada Proyek Pembangunan RSUD Pandan Arang - Fadhilah Arifatunnisa; Budi Priyanto (Pena Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
In the implementation of construction projects, it cannot be separated from problems in project implementation which may be caused by various factors. Of course, in the implementation process there are a number of obstacles that occur in relation to one another and result in other work being disrupted or delayed. This analysis aims to determine the factors that cause obstacles in the Class III Inpatient Building Construction Project of Pandan Arang Hospital. The results of the analysis show that the factors that hinder the completion of the project are the death of heavy equipment used in soil preparation work, hitting a large rock during drilling, flooding during drilling, lack of reinforcing iron fabrication area, porousness during formwork removal, casting carried out during rainy days.